Local Atomic Mechanism for the Diffusion Jump of Carbon Atom in Austenite - Semenov, Michael; Kraposhin, Valentin; Arestov, Vitali; Korolev, Ilya; Pancho-Ramires, Antonio (Diffusion Fundamentals, 2022)
A carbon atom diffusion jump in iron austenite was considered as a subsequence of transformations between the cementite structure and the regular FCC packing. A model of this transformation was based on a 2D model of the elemental act of a polymorph transformation in metals. The energy threshold of this transformation has been calculated using the Morse pair potential. It occurs that the estimated enthalpy of the transformation is equal to 149±20 kJ/mole which is in satisfactory agreement with experimental data.